Tuberous breast and predisposition to breast deformity in consanguineous. Issue 1 (30th May 2017) - Dessy, Luca Andrea; De Santo, Liliana; Onesti, Maria Giuseppina; Fallico, Nefer; Mazzocchi, Marco
Abstract: Tuberous breast deformity is a pathologic condition of the breast consisting of a constricting ring at the breast base, reduction in the volume of the breast parenchyma, and herniation of breast tissue through the nipple‐areola complex with areola enlargement. This pathology is generally congenital and has an unknown etiopathogenesis. We report the first observation of tuberous breast deformity in consanguineous. This report suggests the potential role of a genetic base in the development of this deformity. Between May 2008 and March 2011, we observed six female patients from two different families, aged between 18 and 55 years, affected by tuberous breast deformity. The breast deformity was characterized by breast asymmetry in all six cases. Four patients underwent surgery to correct the deformity. Standardized objective measurements of breast and chest were taken. A Visual Analog Scale was used to evaluate patients' and physicians' satisfaction. The first three patients were consanguineous; two were first cousins, and the third was second cousin with one of the above. The other three patients were also from the same family: two sisters and their mother. According to Von Heimburg's classification, the patients presented different degrees of breast deformity. In all operated cases, a good esthetic result with a high satisfaction (average visual analog scale score 9) was achieved. The results remained stable over time and no revisions were needed after the 1‐year follow‐up. The possibility of a parental consanguinity for breast deformities such tuberous breast has never been described in the literature. This report suggests the possible genetic role in the development of tuberous breast deformity. Further studies and genetic tests are required to prove this hypothesis.